Hubungan Tingkat Pengetahuan dan Konsumsi Natrium Terhadap Tekanan Darah Penderita Hipertensi di Wilayah Kerja Puskesmas Cempaka Tahun 2015 - Oklivia Libri; Rijanti Abdurrachim; Dina Mariana; STIKES Husada Borneo; Politeknik Kesehatan Banjarbaru; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Hypertension is a medical condition in which a person experiences an increase in blood pressure above normal. The common thing that occurs in patients with hypertension that is the lack of knowledge about hypertension and sodium consumption. The purpose of this study was to determine the relationship of the level of knowledge and consumption of sodium on blood pressure of hypertensive patients. The study design used is cross sectional, the study population was all patients with hypertension in the Cempaka Health Center. The sample was 75 respondents, while sampling was done by a purposive sampling method. Respondent’s data of sodium intake and level of knowledge obtained from an interview with a questionnaire method for knowledge and food recall for sodium intake data. Blood pressure data obtained from the measurement results using a sphygmomanometer. Based on the results of statistical tests (chi-square test) found that there was no correlation between the level of knowledge with blood pressure (p=0,151) and there is a correlation between the level of sodium intake with blood pressure (p=0,000). From the results of this study concluded that although there was no significant correlation between knowledge and blood pressure, a better knowledge of the disease can help prevent and making treatment more effective. Keeping sodium intake will have a considerable influence in lowering blood pressure.